Chronic intermittent hypobaric hypoxia ameliorates osteoporosis after spinal cord injury through balancing osteoblast and osteoclast activities in rats - Zhang, Li; Yin, Yingchao; Guo, Jialiang; Jin, Lin; Hou, Zhiyong (Frontiers in Endocrinology, 2023)
As a common complication of spinal cord injury (SCI), most SCI patients suffer from osteoporosis. In our previous study, chronic intermittent hypobaric hypoxia (CIHH) could promote bone fracture healing. We speculated that it may act a role in the progression of osteoporosis. The current study purposed to explore the role of CIHH in the osteoporosis triggered by SCI in rats. A SCI-induced SCI model was established by completed transection at T9-T10 spinal cord of Wistar rats. One week after SCI, the rats were conducted to CIHH treatment (PB = 404 mmHg, Po2 = 84 mmHg) 6 hours a day for continuously 7 weeks. The results of X-radiography and Micro-CT assessment demonstrated that compared with sham rats, the areal bone mineral density (BMD), bone volume to tissue volume, volumetric BMD, trabecular thickness, trabecular number, and trabecular connectivity were decreased. Trabecular bone pattern factor, trabecular separation, as well as structure model index were increased at the distal femur and proximal tibia of SCI rats, which were effectively reversed by CIHH treatment. Histomorphometry showed that CIHH treatment increased bone formation of SCI rats, as evidenced by the increased osteoid formation, the decreased number and surface of TRAP-positive osteoclasts. Furthermore, ELISA and real time PCR results showed that the osteoblastogenesis-related biomarkers, such as procollagen type 1 N-terminal propeptide, osteocalcin in serum, as well as ALP and OPG mRNAs in bone tissue were decreased, while the osteoclastogenesis-related biomarkers, including scleorostin in serum and RANKL and TRAP mRNAs in bone tissue were increased in SCI rats. Importantly, the deviations of aforementioned biomarkers were improved by CIHH treatment. Mechanically, the protective effects of CIHH might be at least partly mediated by hypoxia-inducible factor-1 alpha (HIF-1α) signaling pathway. In summary, the present study testified that CIHH treatment ameliorates osteoporosis after SCI by balancing osteoblast and osteoclast activities in rats.